Blood pressure targeting by partial REBOA is possible in severe hemorrhagic shock in pigs and produces less circulatory, metabolic and inflammatory sequelae than total REBOA. Issue 12 (December 2018) - Sadeghi, Mitra; Hörer, Tal M.; Forsman, Daniel; Dogan, Emanuel M.; Jansson, Kjell; Kindler, Csaba; Skoog, Per; Nilsson, Kristofer F.
Highlights: In pREBOA the targeted blood pressure 80–100 mmHg was reached despite severe hemorrhagic shock. The mesenteric blood flow was sustained in pREBOA, while it was completely obstructed in tREBOA. Arterial acidosis was more profound in tREBOA than in pREBOA during the reperfusion period. Anaerobic metabolism, cytokine response and intestinal ischemia were more pronounced in tREBOA than in pREBOA. Abstract: Background: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is an effective adjunct in exsanguinating torso hemorrhage, but causes ischemic injury to distal organs. The aim was to investigate whether blood pressure targeting by partial REBOA (pREBOA) is possible in porcine severe hemorrhagic shock and to compare pREBOA and total REBOA (tREBOA) regarding hemodynamic, metabolic and inflammatory effects. Methods: Eighteen anesthetized pigs were exposed to induced controlled hemorrhage to a systolic blood pressure (SBP) of 50 mmHg and randomized into three groups of thoracic REBOA: 30 min of pREBOA (target SBP 80–100 mmHg), tREBOA, and control. They were then resuscitated by autologous transfusion and monitored for 3 h. Hemodynamics, blood gases, mesenteric blood flow, intraperitoneal metabolites, organ damage markers, histopathology from the small bowel, and inflammatory markers were analyzed. Results: Severe hemorrhagic shock was induced in all groups. In pREBOA the targeted blood pressure was reached. The mesenteric blood flow was sustained in pREBOA, while it was completely obstructed in tREBOA. Arterial pH was lower, and lactate and troponin levels were significantly higher in tREBOA than in pREBOA and controls during the reperfusion period. Intraperitoneal metabolites, the cytokine response and histological analyses from the small bowel were most affected in the tREBOA compared to the pREBOA and control groups. Conclusion: Partial REBOA allows blood pressure titration while maintaining perfusion to distal organs, and reduces the ischemic burden in a state of severe hemorrhagic shock. Partial REBOA may lower the risks of post-resuscitation metabolic and inflammatory impacts, and organ dysfunction.